2023
DOI: 10.1186/s13054-022-04298-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between early nutrition support and 28-day mortality in critically ill patients: the FRANS prospective nutrition cohort study

Abstract: Background Current guidelines suggest the introduction of early nutrition support within the first 48 h of admission to the intensive care unit (ICU) for patients who cannot eat. In that context, we aimed to describe nutrition practices in the ICU and study the association between the introduction of early nutrition support (< 48 h) in the ICU and patient mortality at day 28 (D28) using data from a multicentre prospective cohort. Methods The ‘F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
9

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 74 publications
2
27
0
9
Order By: Relevance
“…Regarding the role of macronutrient intake in critically ill patients, the EFFORT 15 protein and NUTRIREA‐3 RCTs challenged current beliefs about the potential clinical relevance of high‐dose protein and energy targets. Supported by the observational findings of the FRANS and EuroPN study, 16,17 which both indicated potential harmful effects of an aggressive feeding regime in less severely ill patients and potential clinical benefits of a moderate and progressively increased nutrition strategy, both the EFFORT protein and NUTRIREA‐3 trials could not demonstrate a clinical benefit of reaching early nutrition targets. The EFFORT protein RCT did not show clinically meaningful effects of a high‐dose protein strategy while identifying potential harmful effects of high protein in patients with high degrees of organ injury, as reflected by the Sequential Organ Failure Assessment score and those with acute kidney injury.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the role of macronutrient intake in critically ill patients, the EFFORT 15 protein and NUTRIREA‐3 RCTs challenged current beliefs about the potential clinical relevance of high‐dose protein and energy targets. Supported by the observational findings of the FRANS and EuroPN study, 16,17 which both indicated potential harmful effects of an aggressive feeding regime in less severely ill patients and potential clinical benefits of a moderate and progressively increased nutrition strategy, both the EFFORT protein and NUTRIREA‐3 trials could not demonstrate a clinical benefit of reaching early nutrition targets. The EFFORT protein RCT did not show clinically meaningful effects of a high‐dose protein strategy while identifying potential harmful effects of high protein in patients with high degrees of organ injury, as reflected by the Sequential Organ Failure Assessment score and those with acute kidney injury.…”
Section: Resultsmentioning
confidence: 99%
“…The discussion about optimal energy intake timing and dosing has further been boosted by the results of recent studies such as EuroPN [39 ▪ ], FRANS [40 ▪ ], and NUTRIREA-3 [41 ▪ ], which predominantly focused on patients with septic shock, medical, and surgical admission type, respectively. In a nutshell, these trials emphasize that high energy supply and intense nutrition support in the very early phase of critical illness may be associated with worse outcome.…”
Section: Energy Target/supplymentioning
confidence: 99%
“…For critically ill patients in general, the optimal dosing and timing of protein supply is further discussed in the context of recently published trials such as EuroPN [39 ▪ ], FRANS [40 ▪ ], EFFORT Protein [48 ▪ ], and NUTRIREA-3 [41 ▪ ]. Again, in a nutshell, protein supply should be increased progressively throughout the ICU LOS to reach targets as recommended by current international critical care nutrition guidelines [20,21,28 ▪▪ ,29 ▪▪ ].…”
Section: Protein/amino Acid Target/supplymentioning
confidence: 99%
“…Recent clinical trials showed early aggressive NS resulted in potential harms including hyperglycemia, hepatic steatosis, and mortality [5 ▪▪ ,6,7]. On the other hand, energy deficits may result in negative nitrogen balance, increased length of hospital stay, infection, organ, failure, prolonged mechanical ventilation, and mortality [8–13].…”
Section: Introductionmentioning
confidence: 99%